PENGARUH MOTIVASI DAN KOMUNIKASI TERHADAP KINERJA MELALUI KEPUASAN KERJA PEGAWAI BPPKAD KOTA PROBOLINGGO - Hermani, Hermani (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
The aim of this research is to analyze the influence of motivation and communication on performance through job satisfaction of Probolinggo City BPPKAD employees. This research is explanatory research which aims to examine the influence of the mediating role of job satisfaction on employee motivation, communication and performance. This research used a saturated sample using all ASNs at BPPKAD Probolinggo City as respondents, totaling 76 employees. Data collection used a direct survey method with a questionnaire instrument. Next, it will be analyzed using the Partial Least Square (PLS) – Structural Equation Model (SEM) analysis method and technique. The results of the research show that motivation has no significant effect on job satisfaction, communication has a significant effect on job satisfaction, motivation has no significant effect on employee performance, communication has a significant effect on employee performance, job satisfaction has a significant effect on employee performance, motivation has no significant effect through job satisfaction on performance employees and communication have a significant effect through job satisfaction on employee performance.